2014
DOI: 10.1186/s12955-014-0107-2
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life of children and adolescents with congenital adrenal hyperplasia in Brazil

Abstract: BackgroundCongenital Adrenal Hyperplasia (CAH) is an endocrine disorder characterized by enzymatic deficiency in adrenal steroidogenesis, leading to adrenal insufficiency and hyperandrogenism. Patients need continuous hormone replacement therapy, but adequate control has proven challenging, exposing patients to undesirable consequences of both disease and treatment.ObjectiveTo evaluate the health related quality of life (HRQoL) of children and adolescents with CAH due to 21-hydroxylase deficiency.MethodsIn an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 29 publications
3
31
3
Order By: Relevance
“…Varying degrees of impaired QoL have been described [59,60,74,79,[93][94][95][96]. In a few publications, no difference from controls was found [97][98][99] and, in one study, even a better QoL compared to controls was reported [100].…”
Section: Quality Of Lifementioning
confidence: 99%
“…Varying degrees of impaired QoL have been described [59,60,74,79,[93][94][95][96]. In a few publications, no difference from controls was found [97][98][99] and, in one study, even a better QoL compared to controls was reported [100].…”
Section: Quality Of Lifementioning
confidence: 99%
“…Additionally, the chronicity of CAH entails daily medication, close monitoring by parents during childhood, and when needed also by medical health professionals, experiences that in spite of the positive medical benefit of follow-up, have been shown to restrict physical and social development in children with chronic disorders in general [ 53 ]. Whereas some studies have focused on the medical aspects of the condition in males, few studies have explored how CAH could potentially affect these patients' psychological adjustment and quality of life (QoL) [ 54 ]. Consequently, in order to examine whether males with CAH present distinct psychological challenges that would need to be addressed clinically, an updated summary of the literature is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Self rated QoL for children with CAH differ slightly from the proxyratings by their parents (156). The areas affected, as rated by the children, is fatigue, whereas their parents state academic underachievement, impaired physical and emotional health and psychosocial outcomes (157). For adults, the outcome results are mixed.…”
Section: Cahmentioning
confidence: 84%